Inhibition of BRD4 prevents peribronchial fibrosis in mice with cutaneous lewisite exposure - Zeng, Huaxiu; Singh, Pooja; Sinha, Rajesh; Stephens, Crystal T.; Ahmad, Aftab; Athar, Mohammad; Antony, Veena B. (Frontiers in Molecular Biosciences, 2025)
IntroductionArsenicals like lewisite are highly toxic vesicant chemical warfare agents that cause severe skin damage and systemic inflammation. Exposure activates cytokine release, leading to pulmonary injury, including edema, hemorrhage, and in severe cases, Bronchiolitis Obliterans Syndrome (BOS), marked by airway fibrosis and narrowing. The only approved treatment, British anti-lewisite (BAL), has limitations due to toxicity and field administration challenges. BRD4, a BET family protein, regulates inflammatory gene expression, and its inhibition has shown therapeutic potential. CPI-0610 (Pelabresib), a selective BRD4 inhibitor, is currently being explored for its anti-fibrotic and anti-inflammatory effects.MethodsIn a murine model, we evaluated the therapeutic potential of CPI-0610 in mitigating lewisite-induced pulmonary damage. Mice were exposed to a single cutaneous dose of lewisite to induce systemic lung injury. Following exposure, one group of mice received CPI-0610 treatment, while a control group remained untreated. Lung tissues were harvested for molecular and histological analysis. The expression of inflammatory and fibrotic markers, including interleukin-6 (IL-6) and alpha-smooth muscle actin (α-SMA), was quantified via RT-PCR and immunohistochemistry.ResultsTreatment with CPI-0610 significantly reduced the expression of IL-6 and α-SMA in lung tissues of lewisite-exposed mice compared to untreated controls. Histological analysis revealed reduced signs of inflammation, extracellular matrix deposition, and fibrotic remodeling in the CPI-0610 group. These findings indicate a protective effect of BRD4 inhibition on arsenical-induced lung injury.DiscussionOur study provides the first experimental evidence that BRD4 inhibition via CPI-0610 attenuates the development of pulmonary fibrosis following cutaneous lewisite exposure in mice. These results suggest that targeting BRD4 signaling can effectively reduce inflammation and fibrotic progression in the lungs. Given CPI-0610’s favorable clinical safety profile, it holds promise as a novel therapeutic strategy for treating arsenical-induced pulmonary complications, potentially improving outcomes where current countermeasures like BAL fall short. Further studies are warranted to explore its mechanism of action and therapeutic efficacy in broader exposure models.